2021
DOI: 10.3390/antiox10121927
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Avian Semen Extenders with Antioxidants to Improve Semen Quality—Is It an Effective Strategy?

Abstract: Oxidative stress in sperm is a phenomenon related to the increasing rate of oxidation of cellular components and the excessive production of reactive oxygen species (ROS). The high content of polyunsaturated fatty acids in bird sperm cell membranes renders these cells particularly susceptible to lipid peroxidation (LPO). Therefore, to ensure the proper functioning of cells, it is necessary to have a balance between the formation of ROS and the protective action of the antioxidant system. This review aims first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 76 publications
2
26
0
1
Order By: Relevance
“…As direct interaction with ROS [ 49 ] or as a cofactor of glutathione peroxidase [ 50 ] it neutralizes reactive oxygen species (ROS), including H 2 O 2 and lipid peroxides. It has been found that avian semen extenders enriched with GSH, preserved the viability of sperm cells, plasma membrane integrity, functional, kinetic and fertility parameters, suppressed OS in diluted fresh and post-thawed semen [ 28 , [51] , [52] , [53] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As direct interaction with ROS [ 49 ] or as a cofactor of glutathione peroxidase [ 50 ] it neutralizes reactive oxygen species (ROS), including H 2 O 2 and lipid peroxides. It has been found that avian semen extenders enriched with GSH, preserved the viability of sperm cells, plasma membrane integrity, functional, kinetic and fertility parameters, suppressed OS in diluted fresh and post-thawed semen [ 28 , [51] , [52] , [53] ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the application of antioxidants is a good strategy to preserve reproductive capabilities. The effects of various antioxidants, either dietary supplemented or as ingredients of extenders, on avian semen characteristics are well studied [ 12 , 15 , [25] , [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…This might confirm that the quercetin is situated in the midpiece of spermatozoa. Several factors affect the antioxidant action he quercetin, including extender, animal species (Longobardi et al, 2020; Santiani Acosta et al, 2013), the antioxidant type and concentration (Partyka & Niżański, 2021).…”
Section: Mode Of Actionmentioning
confidence: 99%
“…Therefore, external antioxidants and free radical scavenger compound have been assumed to be promising extender supplementation [ 50 ]. The effectiveness of antioxidants including flavonoid quercetin [ 51 ], Mito-TEMPO [ 52 ], serine [ 53 ], SOD [ 54 ], coenzyme Q10 [ 55 ], melatonin [ 56 , 57 ], L -Carnitine [ 58 ], hyaluronic acid [ 59 ], Vitamin E and CAT [ 60 ], herbal extracts like Achillea millefolium [ 61 ], and N-acetyl- L -cysteineare [ 62 ] proved to be effective in decreasing oxidative stress level, increasing membrane functionality, acrosome integrity, and motility of post-thawed rooster sperm.…”
Section: Semenmentioning
confidence: 99%